Determinants of Corporate Actual Cash Taxes Paid: A New Insight: Array - Asien, Etumudon Ndidi (The Journal of Accounting and Management, 2022)
This paper examines the null hypotheses that revenues, profitability, intangible assets, percentage of foreign shareholdings, external auditors, tax haven status and firm size do not associate with corporate actual cash taxes paid. The main results of pooled OLS multivariate suggest that revenue, intangible assets, and percentage of foreign shareholdings are directly and significantly associated with corporate actual cash taxes paid. In particular, revenues, intangible assets, and percentage of foreign shareholdings are found to increase corporate actual cash taxes paid, thereby leading to conservative tax planning schemes that reduce tax avoidance. The result also suggests that Big-4 accountancy firms, tax haven status and firm size are negatively and significantly associated with corporate actual cash taxes paid. It is recommended that the 1) Federal Inland Revenue Service should monitor the revenues and intangible assets of companies through companies’ annual fillings, 2) relevant agencies of government should encourage foreign equity participation in Nigerian companies, and 3) more non-Big-4 accounting firms should be empowered to audit companies’ financial statements.